The Principle of Equality in Diverse States Reconciling Autonomy with Equal Rights and Opportunities - Belser, Eva Maria; Bächler, Thea; Egli, Sandra; Zünd, Lawrence (Studies in Territorial and Cultural Diversity Governance, 2021)
This book examines different approaches by which states characterised by federal or decentralized arrangements reconcile equality and autonomy. In case studies from four continents, leading experts analyse the challenges of ensuring institutional, social and economic equality whilst respecting the competences of regions and the rights of groups.. Readership: All those interested in federalism, decentralisation and other forms of diverse states and their practical and theoretical implications.